Mecanismos de controle da variação sazonal da transpiração de uma floresta tropical no Nordeste da Amazônia - SOUZA FILHO, José Danilo da Costa (Instituto Nacional de Pesquisas da Amazônia, 2013)
In the present work we study the seasonal variation of the transpiration of a tropical forest, and its dependence on biotic and abiótic factors. We used data of the project CARBOPARÁ, part of The Large Scale Biosphere-Atmosphere Experiment in Amazonia (LBA), collected in the National Forest of Caxiuanã, northeastern Amazonia. The average transpiration in a 39-day period during the rainy season was 2.9 mm day-1. In a 29-day period during dry season, the average transpiration was 4.3 mm day-1. The maximum values of the surface conductivity (Cs) are 0.060 m s-1 and 0.045 m s-1 for the rainy and dry period, respectively, observed at 08:00 h local time. The aerodynamic conductance averages (Ca) 0.164 m s-1 and 0.210 m s-1, for the rainy and dry periods, respectively, while the maximum values of Ca are 0.220 and 0.375 m s-1, for the same periods, respectively. It was verified that Cs presents an inverse exponential relationship with the deficit of atmospheric water vapor, for different intervals of global solar irradiance. The hourly analysis of the decoupling factor suggests that the morning transpiration is mainly controlled by the availability of energy. During the afternoon, on the other hand, for both periods studied, the forest becomes progressively coupled to the atmosphere, denoting larger superficial control on the transpiration process.